A Scalable Isolated Gate Driver With Programmable Frequency and Duty Cycle for Series-Connected SiC MOSFETs - Sohrab Ghafoor; Mahesh Kulkarni; Reza Mirzadarani; Peter Vaessen; Mohamad Ghaffarian Niasar (IEEE Open Journal of the Industrial Electronics Society)
To enhance the voltage-handling capability of a switch, the series connection of switching devices is a cost-effective method that preserves many advantages of mature low-voltage devices. Dynamic voltage imbalance and electrical isolation for the devices at the high voltage (HV) side are two important challenges associated with series connection topology. Transformer-coupled gate drivers are excellent for providing both dynamic voltage balance and high galvanic isolation. However, they can only provide the switching function at the transformer pulse frequency. To generate complex waveforms of future power-electronics-dominated grids, a switch with user-defined turn-on/off timing is required for testing grid assets under high-voltage conditions. This article presents a simple, cost-effective open-loop gate driver that overcomes this limitation by introducing two sets of complementary pulse transformers to initialize programmable frequency and duty cycle. Successful experimental verification of the series-connected SiC mosfets prototype is performed at 3.2 kV at various frequencies and duty cycles. The article also demonstrates that the measurement probes placed across series-connected mosfets significantly affect the voltage distribution and validate a compensation mechanism.